Principles of sociological inquiry : qualitative and quantitative methods - Blackstone, Amy; Saylor Foundation; BC Open Textbook Project; BCcampus (Saylor Foundation, 2014)
"Principles of Sociological Inquiry: Qualitative and Quantitative Methods emphasizes the relevance of research methods for the everyday lives of its readers, undergraduate students. Each chapter describes how research methodology is useful for students in the multiple roles they fill: (1) as consumers of popular and public information, (2) as citizens in a society where findings from social research shape laws, policies, and public life, and (3) as current and future employees. Connections to these roles are made throughout and directly within the main text of the book. Principles of Sociological Inquiry: Qualitative and Quantitative Methods also provides balanced coverage of qualitative and quantitative approaches by integrating a variety of examples from recent and classic sociological research. The text challenges students to debate and discuss the strengths and weaknesses of both approaches."--BCcampus website.
This work is licensed under the Creative Commons Attribution-NonCommercial-ShareAlike License.
Title from BC Campus Website.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Description based on version viewed on BCcampus OpenEd website; title from pdf title page.
Keywords: Sociology -- Research -- Textbooks; Electronic books